2020
DOI: 10.1038/s41598-020-59974-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of variations within the rumen metaproteome of Holstein dairy cattle relative to morning feed offering

Abstract: few studies have utilized proteomic techniques to progress our knowledge of protein-mediated pathways within the rumen microbial community, and no previous research has used these techniques to investigate the patterns or variations of these proteins within this community. it was hypothesized that there would be fluctuations of rumen microbial protein abundances due to feed intake-mediated nutrient availability and that these could be identified using non gel-based proteomic techniques. This study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…In the current work, we optimize the procedure for extraction and identification of rumen proteins that, when compared to previous studies, allowed us to substantially improve the number of proteins identified [23,[46][47][48]. We investigated the rumen microbiome state through its produced proteome profile and its link to the host feed efficiency phenotype, previously Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In the current work, we optimize the procedure for extraction and identification of rumen proteins that, when compared to previous studies, allowed us to substantially improve the number of proteins identified [23,[46][47][48]. We investigated the rumen microbiome state through its produced proteome profile and its link to the host feed efficiency phenotype, previously Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Every sample was collected ~5 hr after the onset of morning feeding on a single day. Access to the rumen via the cannula is described by Honan and Greenwood (2020) and approved by the Institutional Animal Care and Use Committee of the University of Vermont (protocol no. 201900019).…”
Section: Sample Collectionmentioning
confidence: 99%
“…Protein identification and quantification were performed on a Q-Exactive Plus MS coupled to an EASY-nLC 1200 (Thermo Scientific), similar to the workflow described by Honan and Greenwood (2020). Briefly, the fractionated peptide samples were dissolved in 10 μL of 2.5% formic acid (FA) and 2.5% acetonitrile (ACH) in water and then loaded onto a 100-μm × 500-mm capillary column packed with Halo C18 (2.7-μm particle size, 90-nm pore size, Michrom Bioresources) at a flow rate of 300 nL/min.…”
Section: Liquid Chromatography-tandem Ms Analysismentioning
confidence: 99%
“…Previous research by Snelling and Wallace (2017) and Hart et al (2018) provided the first glimpses of microbe-specific proteins in the rumen using gel-based proteomic techniques. Recent modifications by Honan and Greenwood (2020) eliminated the use of gels to expand the breadth of proteins identified in the rumen meta-proteome. This modified approach was applied in this study as a tool to characterize shifts in the meta-proteome in response to dietary carbohydrate profile changes.…”
Section: Introductionmentioning
confidence: 99%